1995
DOI: 10.1111/j.1365-3083.1995.tb03543.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐α Production and Tissue Localization of Interferon‐α/β Producing Cells after Intradermal Administration of Aujeszky's Disease Virus–Infected Cells in Pigs

Abstract: Intradermal administration of glutaraldehyde-fixed Aujeszky's disease virus (ADV) infected autologous or allogeneic cells resulted in the induction of an interferon (IFN)-alpha response in pigs. Using a sensitive dissociation-enhanced lanthanide fluoroimmunoassay (DELFIA), IFN-alpha was detected in blood at 8 and 24 h after injection of ADV-infected cells. In parallel, by means of in situ hybridization, IFN-alpha/beta mRNA containing cells were demonstrated in regional lymph nodes. Occasional IFN-alpha/beta mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Previous studies have shown that IFN-α SC are mainly detected in the lymphoid tissues such as the spleen or regional lymph nodes following non-infectious virus injection (Artursson et al, 1995 ;Splichal et al, 1995 ;Eloranta et al, 1996 ;Riffault et al, 1996). However, this is the first demonstration that circulating PBMC did not produce a detectable amount of IFN-α in vivo.…”
Section: Tissue Of Origin Of Cells Ex Vivo In Vitromentioning
confidence: 41%
See 1 more Smart Citation
“…Previous studies have shown that IFN-α SC are mainly detected in the lymphoid tissues such as the spleen or regional lymph nodes following non-infectious virus injection (Artursson et al, 1995 ;Splichal et al, 1995 ;Eloranta et al, 1996 ;Riffault et al, 1996). However, this is the first demonstration that circulating PBMC did not produce a detectable amount of IFN-α in vivo.…”
Section: Tissue Of Origin Of Cells Ex Vivo In Vitromentioning
confidence: 41%
“…IFN-α SC were accordingly detected in the spleen or the draining lymph node following intravenous (i.v.) or subcutaneous injection of UV-inactivated virus, respectively (Artursson et al, 1995 ;Eloranta et al, 1996 ;Riffault et al, 1996).…”
mentioning
confidence: 99%
“…[24,45]. IFN-P is produced in large amounts by keratinocytes in human skin, and IFN-P mRNA can be detected in skin-draining LN after intradermal injection of virus-infected cells [46]. IFN-alp produced in the draining LN or transported to LN via afferent lymph may promote L-selectin expression which is otherwise lost during primary Tcell activation.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a in cell culture supernatants was quantified by a dissociation-enhanced lanthanide fluoro-immunoasssay (DELFIA), as described previously (Artursson et al, 1995). DELFIA, which is based on two mAbs directed to porcine IFN-a, had a detection limit of 0?3 U IFN-a ml…”
mentioning
confidence: 99%